Metal coordination induced ring contraction of porphyrin derivatives. Issue 71 (17th August 2018) - Patra, Bratati; Sobottka, Sebastian; Mondal, Sruti; Sarkar, Biprajit; Kar, Sanjib
Abstract : Ferrocenyl-porphyrin derivatives upon treatment with silver acetate at room temperature show ring contraction followed by Ag-chelation. Abstract : A remarkable rearrangement of a diferrocenylporphyrin to give a silver(iii ) corrole has been discovered. Compared to the previously reported porphyrin to corrole ring conversions (extremely rare and poor reaction yields), our methodology delivers near quantitative yield for this ring contraction.